HIV prevention for young people in Sub-Saharan Africa: effectiveness of interventions and areas for improvement. Evidence from Rwanda - Michielsen, Kristien (Afrika Focus, 2012)
These conclusions and recommendations mainly affect five parties: researchers, intervention managers, evaluators, funders and scientific journal editors. Given the absence of a vaccine or a cure, the focus remains on preventing HIV transmission. By analysing existing data on the determinants of the complex sexual behaviour of young people and their causal pathways, and by gathering additional information, researchers should make unprecedented efforts to develop alternative and more effective interventions. Accepting the complexity of sexual behaviour of young people, also means dealing with a considerable degree of uncertainty and flexibility. Intervention development, impleme tation and evaluation are to be considered inseparable: results of effectiveness evaluations should be considered of little use if no information is provided on the intervention or its implementation and vice versa. Since the evaluation should be an integral part of the intervention, intervention managers and evaluators need to work in close collaboration, without suspicion. Donors have to accept that a complex intervention cannot be designed beforehand, but requires a process approach that maps risky behaviours, dominant predictors, causal pathways and key stakeholders. This pre-intervention research should be considered a fundamental part of the intervention and donors should be aware that effectiveness depends on this phase, hence funding should be made available. In this process, reality, and not morality, should be at the forefront: young people should be approached as responsible individuals who are able to make their own decisions and need to be made competent to ensure their choice to (not) have sexual intercourse is made autonomous, without coercion or regret and with the necessary in-depth knowl- edge of risks. This requires a change in attitudes of all stakeholders involved. A complex intervention approach also means that the intervention is monitored and can be changed during its course, resulting in the need for flexible, mixed and triangulated evaluation approaches (“combination evaluation”) and flexible funding strategies. Scientific journals have the responsibility to make innovative approaches public, even though they might not be considered most rigorous by current scientific standards, as well as allow for elaborate reports on intervention development and implementation. We are convinced this can be done if all parties remain conscious of the ultimate objective; eradicating HIV among the important and vulnerable population of young people.